Habits of the heartland : small-town life in modern America - Macgregor, Lyn Christine, 1973- (Cornell paperbacks., 2010)
Although most Americans no longer live in small towns, images of small-town life, and particularly of the mutual support and neighborliness to be found in such places, remain powerful in our culture. In this work, the author investigates how the residents of Viroqua, Wisconsin, population 4,355, create a small town community together. She lived in Viroqua for nearly two years. During that time she gathered data in public places, attended meetings, volunteered for civic organizations, talked to residents in their workplaces and homes, and worked as a bartender at the local American Legion post. Viroqua has all the outward hallmarks of the idealized American town; the kind of place where local merchants still occupy the shops on Main Street and everyone knows everyone else. On closer examination, one finds that the town contains three largely separate social groups: Alternatives, Main Streeters, and Regulars. These categories are not based on race or ethnic origins. Rather, social distinctions in Viroqua are based ultimately on residents' ideas about what a community is and why it matters. These ideas both reflect and shape their choices as consumers, whether at the grocery store, as parents of school-age children, or in the voting booth. Living with, and listening to, the town's residents taught the author that while traditional ideas about "community," especially as it was connected with living in a small town, still provided an important organizing logic for peoples' lives, there were a variety of ways to understand and create community. -- From back cover.